Feminist paratextual (re)framing of online social translation - Cheng, Xiaoyi (John Benjamins Publishing Company, 2026)
This study focuses on a range of paratexts around an influential social media account in China named @subtitle girl, who dedicates herself to online feminist content production in the form of (editing) and subtitling feminist clips from English to Chinese. The study aims to identify how the feminist subtitled clips are paratextually (re)framed in the context of digital feminism. The study adopts a suitable theoretical conceptualization of paratextuality and views @subtitle girl’s translational activities under the online social translation/subtitling rubric. Different paratexts around @subtitle girl’s subtitling are examined on the macro and micro level. It is found that, on the macro level, the factual paratextual elements avatar, username, and short bio of @subtitle girl, and algorithm-generated statistics about their subtitling facilitate a (post-)feminist (self-)branding and (self-)promotion of their subtitled work. On the micro level, the hashtagged synopsis for each clip and the comments introduce, highlight, reconstruct, and repackage the subtitled feminist content for the Chinese female audience online. The study shows how the feminist (re)framing on two levels of @subtitle girl’s online social translation/subtitling is fulfilled against the backdrop of digital feminist content production: both the (self-)marketing of the producer/subtitler and the interaction between the producer/subtitler and their AV content consumers and among their consumers are valued.
© Fédération Internationale des Traducteurs (FIT) Revue Babel